2005
DOI: 10.1002/bit.20506
|View full text |Cite
|
Sign up to set email alerts
|

Use of microelectrodes to investigate the effects of 2‐chlorophenol on microbial activities in biofilms

Abstract: In order to assess the applicability of using microelectrodes as a tool for inhibition tests, temporal and spatial inhibitory effects of 2-chlorophenol (2-CP) on O 2 respiration and nitrification activities in municipal wastewater biofilms were investigated using microelectrodes for O 2 and NH 4 þ . The time-course microelectrode measurements demonstrated that 2-CP inhibited O 2 respiration and nitrification activities within 6-18 min. The microbial activities were inhibited only in the upper 400 mm of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We measured the oxygen community metabolism with microelectrodes to check the effect of toxic compounds on biofilms as performed by Satoh et al (2005). Our goal was to show that this approach can also be applied successfully for the study of the effect of natural bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the oxygen community metabolism with microelectrodes to check the effect of toxic compounds on biofilms as performed by Satoh et al (2005). Our goal was to show that this approach can also be applied successfully for the study of the effect of natural bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The mass balance suggested that 2-chlorophenol was mainly mineralized (82%). Satoh et al (2005) evaluated the effect of 10 mg/L of 2-CP on nitrifying biofilm, observing that this compound inhibited the aerobic respiration and 2-CP consumption. On the other hand, Martí-nez-Hernández et al (2011) also evaluated the effect of 2-CP on nitrification process, using nitrifying sludge physiologically stable without previous exposition to any phenolic compound.…”
Section: Tablementioning
confidence: 99%
“…The 2-CP specific consumption rate was 0.001 ± 0.0001 mg 2-CP-C (mg protein-d) −1 . Satoh et al [9] evaluated the effect of 2-CP (10 mg L −1 ) on a nitrifying biofilm, finding that both O 2 and nitrifying consumption rates were inhibited and the 2-CP was not consumed by the biofilm. These results are contrasting with our assays, as the nitrifying sludge was able to consume the 2-CP.…”
Section: Assaysmentioning
confidence: 99%
“…Nevalainen et al [8] studied the elimination of 2,4,6-trichlorophenol (2,4,6-CP) using a nitrifying fluidized-bed reactor, reporting the removal of 2,4,6-CP, but neither the ammonia specific consumption rate nor nitrifying yield values were determined. Satoh et al [9] evaluated the effect of 2-CP on a nitrifying biofilm, observing a decrease in oxygen and ammonium consumption rate and no 2-CP consumption. The objective of this work was to determine the effects of 2-CP on the nitrifying sludge using response variables such as specific rates and yields as well as to obtain evidences of the level to which this compound acts.…”
Section: Introductionmentioning
confidence: 99%